ANALISIS PETA RISIKO PENGEBORAN DI WILAYAH ASSET 5 PT PERTAMINA EP - Gondo Irawan; Berto Mulia Wibawa (Jurnal Manajemen dan Kewirausahaan, 2015)
The purposes of this study were to analyze problem maps in drilling activity, identifying and mapping drilling risks, and analyze risk management strategy which should be prepared for drilling activity. The research was conducted at the TJG-HZ1 wells, Asset 5 Region PT Pertamina EP, South Kalimantan. The tools used measurement and mapping risks according to Godfrey (1996). Data collection consisted of five stages: observation, interview, questionnaire, literature review, and focus group discussion. The results showed there are 24 identified risks which were divided into four risk categories which is financial, strategic, operational, and hazard. From the 24 risks, there were eight risks in the extreme level, five risks in the high level, five risks in the medium level, and six risks in the low level.